Smart video conference over wifi / Mohd Afiq Othman Zailani - Othman Zailani, Mohd Afiq (2009)
Desktop and mobile application has become needed in people's life because it can help people to complete in everyday's task much easier. The applications created nowadays are very useful and it can be enhance in the future to be more functional as the people request. The researcher has developed a Smart Video Conference application for those who need this technology to accomplish any task. This Smart Video Conference will be a compatible platform for the desktop and mobile to have a video chatting at the same time. Both devices will support its features. The researcher developed this application in php programming language using Macromedia Dreamweaver and chooses Apache HTTP Server and Adobe Media Flash Server as the gateway for this application to connect. As a conclusion, this Smart Video Conference application will continue to become more thoroughly integrated and comprehensive tool for users those need it. However, this will not be fully realized until developers begin to develop creative and interesting applications that utilize the video conference technology that can support both desktop and mobile platform instantly.